A prospective clinical study of feto-maternal outcome in pregnancies with abnormal liquor volume - Chavda, Rutwa J.; Saini, Hardev B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Evaluating feto-maternal outcome in pregnancies with abnormal liquor volume. Methods: 200 pregnant subjects between 20 and 42 weeks of gestation, who were clinically suspected to have an abnormal amniotic fluid volume (oligohydramnios or polyhydramnios) were subjected to ultrasonographic (USG) assessment of amniotic fluid index. The subjects were closely monitored during pregnancy, labour and puerperium. Results: Ultrasonically, abnormal liquor volume was confirmed in 90-93% clinically suspected patients. Post term pregnancy (39%), PROM (30%) and prolonged pregnancy (24%) were associated with oligohydramnios. Fetal congenital anomalies (31%), diabetes mellitus (20%), PIH (18%), twin pregnancy (7%) and Rh incompatibility (4%) were associated with polyhydramnios. The incidence of labour induction, fetal labour intolerance, CS for fetal distress and 1 min APGAR of <7 was high in oligohydramnios -subjects. Premature labour complicated 40% of polyhydramnios pregnancies. The overall incidence of congenital anomalies (14%) and perinatal mortality (20%) in subjects with abnormal liquor volume was significantly higher (P<0.001) than in women with normal liquor volume (0.3, 2.3% respectively). Conclusions: A good clinical examination can pick up most subjects of abnormal liquor volume. Abnormal liquor volumes are associated with increased maternal morbidity and adverse perinatal outcome.